مقومات الهوية الوطنية في مواثيق الثورة الجزائرية - بن تيشة, حسن (جامعة الوادي University of Eloued, 2017)
تعد مواثيق الثورة الجزائرية المصادر الأساسية الأولى في معرفة أهداف ومبادئ والتوجهات السياسية للثورة ,وتعتبر هذه النصوص البرنامج الثوري والنظرة المستقبلية للبلاد ,وتتمثل هذه المواثيق في النصوص الثلاث بيان أول نوفمبر مؤتمر الصومام وبرنامج طرابلس, وتعد مسألة الهوية ركيزة القضايا التي تطرقت إليها. ومن خلال هذا المقال نريد معرفة مقومات الهوية الوطنية استنادا إلى هذه النصوص الثورية ومنه يمكن طرح الإشكالية التالية: كيف كان تصور الهوية في نظرة معدي مواثيق الثورة الجزائرية The charters of algerian ravolutoion is considered as the first resourses to knowthe obgectives brincibals bolitical orientation of the revolution.and this texts is considered as the program s ravolutoion and the outlook mani of the contry and these charters are represented by the three texts the statement of.November the soummam conferance tripoli program.and the issue of identity is the cornerstone of the ones that have touched upon it through this article we want to know the fundamentals of national identity based on these revolutionary texts from which can be raised the following problem: how was the perception of identity in the authors views the protocols of the algerian revolution.
مقال
Keywords: مواثيق، الثورة الجزائرية، مؤتمر الصومام، الهوية